The ecology of dust. Issue 8 (12th October 2009) - Field, Jason P; Belnap, Jayne; Breshears, David D; Neff, Jason C; Okin, Gregory S; Whicker, Jeffrey J; Painter, Thomas H; Ravi, Sujith; Reheis, Marith C; Reynolds, Richard L
Abstract : Wind erosion and associated dust emissions play a fundamental role in many ecological processes and provide important biogeochemical connectivity at scales ranging from individual plants up to the entire globe. Yet, most ecological studies do not explicitly consider dust‐driven processes, perhaps because most relevant research on aeolian (wind‐driven) processes has been presented in a geosciences rather than an ecological context. To bridge this disciplinary gap, we provide a general overview of the ecological importance of dust, examine complex interactions between wind erosion and ecosystem dynamics from the scale of plants and surrounding space to regional and global scales, and highlight specific examples of how disturbance affects these interactions and their consequences. It is likely that changes in climate and intensification of land use will lead to increased dust production from many drylands. To address these issues, environmental scientists, land managers, and policy makers need to consider wind erosion and dust emissions more explicitly in resource management decisions.